KNOWLEDGE GAIN BY FARM WOMEN IN A TRAINING ON DUCK FARMING (Indian Journal of Animal Production and Management, 2014)
ZA study was conducted on 50 farm women of Kamrup district of Assam, who attended training programmed on “Scientific Duck Farming” organized and conducted by Livestock Research Station, Mondira from 4th to 5th April, 2013. A structured interview schedule was prepared to study the personal characteristics of the farm women and to list their knowledge level on Scientific Duck Farming before and after training programme. The reliability of the instrument was tested on non-sample respondents with test-retest method. The findings revealed that majority of the trainees reported to acquire medium knowledge gain during training course. On the other hand relational analysis revealed that out of the seven variables only one variable i.e. education was found to have significant correlation with knowledge gain. Multiple regressions showed that out of the seven variables only three variables could significantly contribute to knowledge gain. These were income source, education and information source. These variables together could explain 50 per cent of the variation in knowledge gain (R2 = 0.5097).
Keywords: Knowledge gain; farm women; training